Encyclopedia of Polymer Science and Technology 2011
DOI: 10.1002/0471440264.pst295.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethanes

Abstract: Polyurethanes are among the most widespread polymer technologies and account for about 5% of all plastics produced worldwide. This review covers the technology of polyurethane building block production and physical properties, the fundamental science underlying reactivity and polymer properties and industrial applications. Specifically covered are isocyanates, polyols, elastomers, foams, coatings, adhesives, thermoplastics, recycling, and health and environmental issues. Industrial size, participants, and tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
103
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(104 citation statements)
references
References 120 publications
1
103
0
Order By: Relevance
“…Accounting for about 5% of all plastics produced worldwide, polyurethanes (PU) are among the most widespread polymer technologies [1]. Formed by reacting a di-or polyisocyanate with a polyol containing on average two or more hydroxyl groups, spray polyurethane foams (SPF) cured by atmospheric moisture are widely (and increasingly) [2] utilized in the construction industry for installing door and window frames, to seal gaps in roof constructions and to fix polystyrene and polyurethane panels to walls and insulate buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Accounting for about 5% of all plastics produced worldwide, polyurethanes (PU) are among the most widespread polymer technologies [1]. Formed by reacting a di-or polyisocyanate with a polyol containing on average two or more hydroxyl groups, spray polyurethane foams (SPF) cured by atmospheric moisture are widely (and increasingly) [2] utilized in the construction industry for installing door and window frames, to seal gaps in roof constructions and to fix polystyrene and polyurethane panels to walls and insulate buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 and Table 3 show the chemical structures of U, T, and E and the designations and compositions of the samples used for the model system. Based on previous reports [22], it is known that urethane forms three different types of hydrogen bonds (free (noN-Hydrogen bonded), single-hydrogen bonds, and double-hydrogen bonds) [21,23]. As shown in Figure 5a, the FT-IR spectrum of U100 (pure U) showed the double-hydrogen bonded C=O band at 1690.3 cm −1 , the single-hydrogen bonded C=O band (about 1715.0 cm −1 ) as a shoulder, and the free C=O band (about 1740.6 cm −1 ) as a weak shoulder (barely detectable).…”
Section: Optical Propertiesmentioning
confidence: 98%
“…It is also noted that in contrast to intrinsic systems, it is difficult for the extrinsic systems to maintain the initial optical properties after the self-healing process because of the large difference in the color and refractive index between the intact matrix and the healed region. For these reasons, it is concluded that intrinsic systems are a more appropriate solution for applications, such as in display technologies, that require excellent optical properties.Polyurethane is a widely used intrinsic self-healing material that has been extensively studied because it can effectively recover from the dents on the surface due to its high elasticity [17][18][19][20][21]. However, while polyurethane can self-heal the dents on its surface, it cannot fully heal the scratch damage areas due to the lack of a strong specific interaction between the polyurethane chains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Polyurethanes find frequent uses because of attractive properties such as resistance to corrosion, good dielectric properties, high strength, and toughness. [1][2][3][4] More specifically, polyurethanes are regularly utilized as protection for wires in electrical appliances but have also found many other uses in the industry ranging from shoe sole foam to biomedical applications. [5][6][7][8][9] Other interesting applications include alternative insulation to large structures such as refrigerated vehicles.…”
Section: Introductionmentioning
confidence: 99%